2008
DOI: 10.1097/fpc.0b013e3282f55e2e
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of human xanthine oxidase allelic variants

Abstract: These results suggest that several single nucleotide polymorphisms in the XO gene are involved in individual variations in XO activity. In addition, such findings will be useful to identify xanthinuria patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
62
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 37 publications
8
62
3
Order By: Relevance
“…38 Variation in TPMT and XO activity across ethnic groups have been described which may affect the metabolism of thiopurines. 39,40 However, there is no published information about any difference in the frequency of ''selective MMP shunters'' or response to the allopurinol-thiopurine combination therapy across populations.…”
Section: Discussionmentioning
confidence: 99%
“…38 Variation in TPMT and XO activity across ethnic groups have been described which may affect the metabolism of thiopurines. 39,40 However, there is no published information about any difference in the frequency of ''selective MMP shunters'' or response to the allopurinol-thiopurine combination therapy across populations.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the rarity of functional genetic variations in the XO gene [20], sex and cigarette smoking have been widely investigated as a possible determinants of XO activity. Most of the previous studies did not observe any correlation between sex and enzyme activity [19,21,22,43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies, using radiochemical assay [13] or caffeine test [11,14,18,19], showed that XO activity differs among individuals. Known functional genetic variations in the XO gene are rare [20]. Although environmental factors seem to be responsible for the described variability [15,17,19], it is generally accepted that cigarette smoking does not affect XO activity [11,19,21].…”
Section: Introductionmentioning
confidence: 99%
“…Kudo et al 16 defined variations in a group of 96 Japanese. Several polymorphisms were defined, which correlated with individual differences in XO enzyme activity.…”
Section: Implications For the Asia-pacific Regionmentioning
confidence: 99%